Quiz 21 Flashcards
How do you use (∃x∈A) P(x) in a proof?
Use x∈A where x is generic. Use P(x).
What is the following inference rule called?
P(x) where x can be anything you choose
∴ ∃x P(x)
Existential Generalization
Select a reasonable strategy for proving ∀x P(x)
Prove P(x) where x is generic.
Which of the following is called Universal Instantiation?
∀x P(x)
∴ P(x) where x can be anything you choose
Select all reasonable strategies for proving q → p
Assume q. Prove p.
Assume ¬p. Prove ¬q
Assume q. Assume ¬p. Prove 0.
What is the following inference rule called?
x∈A → P(x) where x is generic
∴ (∀x∈A) P(x)
Universal Generalization
How might you use ∃x P(x) in a proof?
Existential Instantiation
Which rule of inference justifies the final step in a typical proof of (∀x∈A) P(x)?
Universal Generalization
How might you use p → q in a proof of p?
You can’t.
Select a reasonable strategy for proving (p → q) → r
Assume p → q. Prove r.
Select all reasonable strategies for proving p.
Use the definition of p.
Assume ¬p. Prove 0.
Assume ¬p. Prove p.
How do you use ∀x P(x) in a proof?
Use P(x) where x is whatever you want it to be.
Select all reasonable strategies for proving (p ∨ q) → r
Prove p → r. Prove q → r. Part 1: Assume p. Prove r. Part 2: Assume q. Prove r. Part 1: Assume q. Prove r. Part 2: Assume p. Prove r.
Select a reasonable strategy for proving (∃x∈A) P(x)
Prove x∈A where x is anything you want it to be. Prove P(x).
Which of the following is called Existential Instantiation?
∃x P(x)
∴ P(x) where x is generic
Select all reasonable strategies for proving p ↔ q.
Prove p → q. Prove q → p. Prove p → q. Prove ¬p → ¬q. Part 1: Assume p. Prove q. Part 2: Assume q. Prove p. Part 1: Assume q. Prove p. Part 2: Assume p. Prove q.
Select all reasonable strategies for proving (∀x∈A) P(x)
Prove x∈A → P(x), where x is generic.
Assume x∈A where x is generic. Prove P(x).
How might you use p → q in a proof of ¬p?
Modus tollens.
Which rule of inference justifies the final step in a typical proof of ∃x P(x)?
Existential Generalization
How might you use (∃x∈A) P(x) in a proof?
Existential Instantiation
What is the following inference rule called?
(∃x∈A) P(x)
∴ x∈A ∧ P(x) where x is generic
Existential Instantiation
Select a reasonable strategy for proving ∃x P(x)
Prove P(x) where x is whatever you want it to be.
What is the following inference rule called?
(∀x∈A) P(x)
x∈A where x can be anything you choose
∴ P(x)
Universal Instantiation
Universal Modus Ponens
How might you use ∀x P(x) in a proof?
Universal Instantiation
Select a reasonable strategy for proving (p ∧ q) → r
Assume p. Assume q. Prove r.
Select a reasonable strategy for proving p ∧ q
Prove p. Prove q.
How might you use p → q in a proof of q?
Modus ponens.
What is the following inference rule called?
P(x) where x is generic
∴ ∀x P(x)
Universal Generalization
Which of the following is called Existential Generalization?
P(x) where x can be anything you choose
∴ ∃x P(x)
How do you use p ∧ q in a proof?
Use p. Use q.
What is the following inference rule called?
P(x) where x can be anything you choose
x∈A
∴ (∃x∈A) P(x)
Existential Generalization
Select all reasonable strategies for proving ¬p.
Use the definition of p.
Assume p. Prove 0.
Assume p. Prove ¬p.
Which of the following is called Universal Generalization?
P(x) where x is generic
∴ ∀x P(x)
Which of the following are valid inference rules?
First 4
∀x P(x)
∴ P(x) where x can be anything you choose
P(x) where x is generic
∴ ∀x P(x)
∃x P(x)
∴ P(x) where x is generic
P(x) where x can be anything you choose
∴ ∃x P(x)
How do you use ∃x P(x) in a proof?
Use P(x) where x is generic
Which rule of inference justifies the final step in a typical proof of ∀x P(x)?
Universal Generalization
What is the following inference rule called?
∃x P(x)
∴ P(x) where x is generic
Existential Instantiation
What is the following inference rule called?
∀x P(x)
∴ P(x) where x can be anything you choose
Universal Instantiation
Which rule of inference justifies the final step in a typical proof of (∃x∈A) P(x)?
Existential Generalization
How do you use (∀x∈A) P(x) in a proof?
Prove x∈A where x is anything you want it to be. Use P(x).
How might you use p → q in a proof of ¬q?
You can’t.